Odpowiedzi

2009-12-05T19:42:47+01:00
Witaj:)
A) (x+1)(x-2)+(x+2)(x-1)= x²-2x+x-2+x²-x+2x-2=2x²-2
b) (5K+N)(K-2N)-K(4K+N)= 5K²-10KN+KN-2N²-4K²-KN=K²-2N²-10KN
C) (4Y+3)(Y-2)-2Y(4-2Y) = 4Y²-8Y+3Y-6-8Y+4Y²=8Y²-13Y-6
1 5 1
Najlepsza Odpowiedź!
2009-12-05T19:45:53+01:00
A) (x+1)(x-2)+(x+2)(x-1) = x^2-2x+x-2+x^2-x+2x-2= 2x^2-2

b) (5K+N)(K-2N)-K(4K+N)= 5K²-10KN+KN-2N²-4K²-KN=K²-2N²-10KN


C) (4Y+3)(Y-2)-2Y(4-2Y) =4y^2-8y+3y-6-8y+4y^2= 8y^2-13y-6
2 4 2
2009-12-05T21:35:39+01:00
A) (x+1)(x-2)+(x+2)(x-1) = x²-2x+x-2+x²-x+2x-2= 2x²-2

b) (5K+N)(K-2N)-K(4K+N)= 5K²-10KN+NK-2N²-4K²-KN=K²-10KN-2N²

C) (4Y+3)(Y-2)-2Y(4-2Y) =4Y²-8Y+3Y-6-8Y+4Y²= 8Y²-13Y-6
1 5 1